A parametric study of seismic behavior of roller seismic isolation bearings for highway bridges. - Ou, Yu-Chen
A roller seismic isolation bearing is proposed for use in highway bridges. The bearing utilizes a rolling mechanism to achieve seismic isolation and has a zero post-elastic stiffness under horizontal ground motions, a self-centering capability, and unique friction devices for supplemental energy dissipation. The objectives of this research are to investigate the seismic behavior of the proposed bearing using parametric studies (1) with nonlinear response history analysis and (2) with equivalent linear analysis according to the AASHTO guide specifications, and by comparing the results from both analysis methods (3) to evaluate the accuracy of the AASHTO equivalent linear method for predicting the peak displacement of the proposed bearing during an earthquake. Twenty eight ground motions are used in the studies. The parameters examined are the sloping angle of the intermediate plate of the bearing, the amount of friction force for supplemental energy dissipation, and the peak ground acceleration levels of the ground motions. The peak displacement and base shear of the bearing are calculated. Results of the studies show that a larger sloping angle does not reduce the peak displacement for most of the parametric combinations without friction devices. However, for parametric combinations with friction devices, it allows for the use of a higher friction force, which effectively reduces the peak displacement, while keeping a self-centering capability. The AASHTO equivalent linear method may underestimate the peak displacement by as much as 40 percent. Vertical ground motions have little effect on the peak displacement, but significantly increase the peak base shear.
Keywords: Seismic; Bridges; Seismic isolation; Roller bearings